Ecological and evolutionary implications of food subsidies from humans. (18th October 2013) - Oro, Daniel; Genovart, Meritxell; Tavecchia, Giacomo; Fowler, Mike S.; Martínez‐Abraín, Alejandro
Abstract: Human activities are the main current driver of global change. From hunter‐gatherers through to Neolithic societies–and particularly in contemporary industrialised countries–humans have (voluntarily or involuntarily) provided other animals with food, often with a high spatio‐temporal predictability. Nowadays, as much as 30–40% of all food produced in Earth is wasted. We argue here that predictable anthropogenic food subsidies (PAFS) provided historically by humans to animals has shaped many communities and ecosystems as we see them nowadays. PAFS improve individual fitness triggering population increases of opportunistic species, which may affect communities, food webs and ecosystems by altering processes such as competition, predator–prey interactions and nutrient transfer between biotopes and ecosystems. We also show that PAFS decrease temporal population variability, increase resilience of opportunistic species and reduce community diversity. Recent environmental policies, such as the regulation of dumps or the ban of fishing discards, constitute natural experiments that should improve our understanding of the role of food supply in a range of ecological and evolutionary processes at the ecosystem level. Comparison of subsidised and non‐subsidised ecosystems can help predict changes in diversity and the related ecosystem services that have suffered the impact of other global change agents.